2020
DOI: 10.1038/s41598-020-77194-9
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface manifestation of COVID-19 and tear film analysis

Abstract: To evaluate the ocular manifestation in patients hospitalized with coronavirus disease 2019 (COVID-19) and to search for the presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in tears. This study was conducted in 29 hospitalized patients who were admitted to the COVID center at the Policlinic Hospital of the University of Messina, Italy. All patients underwent an ophthalmologic assessment comprising a Standardized Patient Evaluation of Eye Dryness (SPEED) questionnaire, anterior segment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 35 publications
0
53
0
14
Order By: Relevance
“…In addition, RNA in the tear fluid of patients with moderate to severe COVID-19 was collected with a conjunctival swab or the Schirmer test, and the differences depending on the collection method were examined. However, the collection rate was similar in either method, and the detection rate of viral RNA in the tears reached 24% [ 47 ], while no viral RNA was detected in the tear fluid in COVID-19 patients [ 86 , 87 ]. Furthermore, the investigation of human post-mortem ocular tissues in COVID-19 patients found that there was no SARS-CoV-2 RNA in the different parts of ocular tissues and intraocular fluid including corneal epithelium, stroma and endothelium, conjunctival epithelium and fluid, and the anterior chamber [ 88 ].…”
Section: Modes Of Transmission and Prevention Of Viral Infectionsmentioning
confidence: 99%
“…In addition, RNA in the tear fluid of patients with moderate to severe COVID-19 was collected with a conjunctival swab or the Schirmer test, and the differences depending on the collection method were examined. However, the collection rate was similar in either method, and the detection rate of viral RNA in the tears reached 24% [ 47 ], while no viral RNA was detected in the tear fluid in COVID-19 patients [ 86 , 87 ]. Furthermore, the investigation of human post-mortem ocular tissues in COVID-19 patients found that there was no SARS-CoV-2 RNA in the different parts of ocular tissues and intraocular fluid including corneal epithelium, stroma and endothelium, conjunctival epithelium and fluid, and the anterior chamber [ 88 ].…”
Section: Modes Of Transmission and Prevention Of Viral Infectionsmentioning
confidence: 99%
“…Ocular involvement in coronavirus disease 2019 (COVID-19) is low and manifests mainly as conjunctivitis, in the form of conjunctival hyperemia, chemosis, increased secretions, and/or epiphora ( 1 3 ). Signs of blepharitis (crusted eyelashes, meibomian orifice alterations, lid margin hyperemia) and eye burning have also been reported ( 4 ). Dry eyes were reported in 72% of patients evaluated for neurotropism of the virus in the head–neck region ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of these ocular signs and symptoms being common in the general population was not checked prior to the onset of COVID-19 impeding the assessment of the correlation with COVID-19. 23 Among three patients with a positive tear sample result studied by Karimi et al , 7 only one patient had symptoms of conjunctivitis. No ocular abnormalities were observed in any patient with COVID-19 included in other studies concerning the ocular involvement, as was the case in our study.…”
Section: Discussionmentioning
confidence: 96%
“…Viral RNA was detected in conjunctival swabs of two patients, both having ocular abnormalities. 9 The presence of SARS-CoV-2 RNA on the ocular surface and ocular manifestations was studied in 29 hospitalised patients with COVID-19 by Meduri et al 23 RNA was not detected in any of the tear samples by RT-qPCR on Schirmer strips, in spite of a high prevalence of mild ocular symptoms (eye burning: n=4; foreign body sensation: n=3; tearing: n=3). Furthermore, mild conjunctival hyperaemia and/or chemosis (n=7) and blepharitis signs (n=11) were often observed.…”
Section: Discussionmentioning
confidence: 99%